Comparing estimates of actual evapotranspiration from satellites, hydrological models, and field data: a case study from Western Turkey - Kite, G.W.; Droogers, Peter (International Water Management Institute, 2000)
An overview of an experiment in which 8 different methods of estimating actual evaporation and transpiration were compared using a common database. Methods based on field data, hydrological models, and satellite data were used and the objectives were to compare results and to assess the utility of each method for various applications.